Dual-scan technique for the customization of zirconia computer-aided design/computer-aided manufacturing frameworks - Andreiuolo, Rafael Ferrone (Medknow Publications & Media Pvt Ltd, 2013)
The use of bi-layered all-ceramic crowns has continuously grown since the introduction of computer-aided design/computer-aided manufacturing (CAD/CAM) zirconia cores. Unfortunately, despite the outstanding mechanical properties of zirconia, problems related to porcelain cracking or chipping remain. One of the reasons for this is that ceramic copings are usually milled to uniform thicknesses of 0.3-0.6 mm around the whole tooth preparation. This may not provide uniform thickness or appropriate support for the veneering porcelain. To prevent these problems, the dual-scan technique demonstrates an alternative that allows the restorative team to customize zirconia CAD/CAM frameworks with adequate porcelain thickness and support in a simple manner.